2022
DOI: 10.3389/fped.2022.883185
|View full text |Cite
|
Sign up to set email alerts
|

Cord Blood SARS-CoV-2 IgG Antibodies and Their Association With Maternal Immunity and Neonatal Outcomes

Abstract: Passive transplacental immunity is crucial for neonatal protection from infections. Data on the correlation between neonatal immunity to SARS-CoV-2 and protection from adverse outcomes is scarce. This work aimed to describe neonatal seropositivity in the context of maternal SARS-CoV-2 infection, seropositivity, and neonatal outcomes. This retrospective nested case-control study enrolled high-risk pregnant women with a SARS-CoV-2 RT-PCR positive test who gave birth at the Instituto Nacional de Perinatología in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…It's well known that, immunglobuline G antibodies can be transferred from mother to baby. In a study conducted that 76% of neonates from seropositive mothers had antibodies against SARS-CoV-2 in cord blood, of whom 56% had a SARS-CoV-2 negative test result at birth (11). Although, a positive association between maternal IgG levels with neonatal IgG levels was observed in that study, the IgG level in this current baby was negative while the IgG level positive in the mother.…”
Section: Discussionmentioning
confidence: 69%
“…It's well known that, immunglobuline G antibodies can be transferred from mother to baby. In a study conducted that 76% of neonates from seropositive mothers had antibodies against SARS-CoV-2 in cord blood, of whom 56% had a SARS-CoV-2 negative test result at birth (11). Although, a positive association between maternal IgG levels with neonatal IgG levels was observed in that study, the IgG level in this current baby was negative while the IgG level positive in the mother.…”
Section: Discussionmentioning
confidence: 69%
“…One of the factors affecting the transplacental antibody transfer ratio is antibody concentrations in maternal blood since, in our study and in previous studies, correlation between maternal and cord blood antibody concentrations was demonstrated. [12][13][14][15][16]20,21 Moreover, previous studies demonstrated that compared with asymptomatic infections, symptomatic infections with SARS-CoV-2 were associated with higher maternal antibody concentrations. 13,14,20,21 In addition, the timing of the infection during the pregnancy affects the antibody transfer.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16]20,21 Moreover, previous studies demonstrated that compared with asymptomatic infections, symptomatic infections with SARS-CoV-2 were associated with higher maternal antibody concentrations. 13,14,20,21 In addition, the timing of the infection during the pregnancy affects the antibody transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored the placental transfer of maternal SARS-CoV-2 specific antibodies following maternal infection, the largest cohort published to dateto our knowledge -evaluated 145 mothers [8][9][10][11][12][13][14][15][16]. There remains a need for more extensive studies to improve our understanding of the complex dynamics of placental transfer of IgG following natural SARS-CoV-2 infection, which may pave the way for advances in vaccination campaigns [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%